Enola Holmes : the Case of the Missing Marquess [Prípad zmiznutého markíza anglicky]. [Book 1] - Springer, Nancy, 1948- (London : HOT KEY BOOKS, 2020)
Meet Enola Holmes, teenaged girl turned detective and the younger sister to Sherlock Holmes.When Enola discovers her mother has disappeared, she quickly embarks on a journey to London in search of her. But nothing can prepare her for what awaits. Because when she arrives, she finds herself involved in the kidnapping of a young marquess, fleeing murderous villains, and trying to elude her shrewd older brothers-all while attempting to piece together clues to her mother's strange disappearance. Amid all the mayhem, will Enola be able to decode the necessary clues and find her mother?
The Enola Holmes Mysteries
Keywords: americké romány; American novels; detektívne romány; Detective novels; cudzojazyčná literatúra; čítanie je IN (11+)